2011
DOI: 10.1111/j.1750-3841.2011.02295.x
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Composite Films of Chitosan, Methylcellulose, and Nanoparticles

Abstract: Plastic is readily available and inexpensive, so it is becoming the main material for packaging. Unfortunately plastics do not biodegrade and, if reduced in small pieces, contaminate soil and waterways. In the present work, natural films composed of chitosan, methylcellulose, and silica (SiO(2)) nanoparticles (NPs) were developed as new packaging materials. The effect of the incorporation of NPs into the polymeric film matrix was evaluated. An excellent improvement of the mechanical properties was obtained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 52 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…MC brings high deformability to the blend due to its elongation at break value of 12.7%, vs. 3.9% for CH. The addition of CH has been seen to increase the solubility of the films in water (Mura et al 2011) and decrease the WVP of the composite (García et al 2009a;Khan et al 2011). In some studies, the WVP of pure MC and CH have been essentially the same; 7.55  0.60·10 -11 g·m/m 2 ·s·Pa and 7.24  0.81·10 -11 g·m/m 2 ·s·Pa, respectively (Pinotti et al 2007).…”
Section: Chitosan-containing MC Filmsmentioning
confidence: 92%
See 2 more Smart Citations
“…MC brings high deformability to the blend due to its elongation at break value of 12.7%, vs. 3.9% for CH. The addition of CH has been seen to increase the solubility of the films in water (Mura et al 2011) and decrease the WVP of the composite (García et al 2009a;Khan et al 2011). In some studies, the WVP of pure MC and CH have been essentially the same; 7.55  0.60·10 -11 g·m/m 2 ·s·Pa and 7.24  0.81·10 -11 g·m/m 2 ·s·Pa, respectively (Pinotti et al 2007).…”
Section: Chitosan-containing MC Filmsmentioning
confidence: 92%
“…MC is soluble in cold water when the degree of substitution is within the range 1.4 to 2.0 (Sjöström 1993). It is non-toxic and forms continuous, flexible, transparent, tasteless films that have good oxygen barrier properties (Mura et al 2011), but it is a poor barrier against water vapor. MC can be used as an edible film or coating, and as a component to modify the mechanical and barrier properties of layered or blended composites for packaging.…”
Section: Methylcellulosementioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to plastic materials, Mura et al reported the excellent improvement in the mechanical properties of a nanostructured film composed of chitosan, methylcellulose and silica nanoparticles which may replace plastic for packaging foods thereby reducing the environmental pollution by plastics [110]. Another interesting work done by de Moura et al show the application of chitosan nanoparticles-carboxymethylcellulose films [111].…”
Section: Chitosan Based Nanocompositesmentioning
confidence: 99%
“…For example, the possible role of chitosan NPs (Corradini et al, 2010;Mura et al, 2011a) and of kaolinbased nanolayers was assessed for slow release of NPK fertiliser, but further investigation is still needed (Ghormade et al, 2010).…”
Section: Applications Of Nanotechnology In the Agricultural Sectormentioning
confidence: 99%